Miscellanea on Encephalopathies - Tanasescu, Radu (IntechOpen, 2012)
The book project "Miscellanea on Encephalopathies" aims to cover some of the important aspects of infectious-related encephalopathies, post-transplantation and drug-induced encephalopathies, by transmitting valuable information filtered through the real life clinical and research experience of the authors.